V/Q SPECT for the Assessment of Regional Lung Function: Generation of Normal Mean and Standard Deviation 3-D Maps - Bourhis, David; Robin, Philippe; Essayan, Marine; Abgral, Ronan; Querellou, Solène; Tromeur, Cécile; Salaun, Pierre-Yves; Le Roux, Pierre-Yves (Frontiers in Medicine, 2020)
Background V/Q SPECT/CT is attractive for regional lung function assessment, but accurate delineation and quantification of functional lung volumes remains a challenge. Physiological intra and inter patient non uniformity of V/Q SPECT/CT images make conventional segmentation methods inaccurate. In that context it would be of interest to build statistical maps of normal V/Q SPECT to assess the physiological variability of radiotracers. The aim of this study was to generate normal mean and standard deviation maps of regional lung function as assessed with V/Q SPECT/CT, with (AC) and without (NoAC) attenuation correction. Methods During a 13 month period, 73 consecutive patients referred for suspected acute pulmonary embolism, that had normal V/Q SPECT/CT based on the interpretation of 2 independent nuclear medicine physicians, were selected. Four set of images were reconstructed: perfusion and ventilation images, AC and NoAC respectively. Statistical maps were created as follows: all cases were registered to a reference scan using the CT data, first with a rigid then with a non-rigid method. SPECTs reconstructions were then co-registered and normalized, and mean and standard deviation voxel-wise maps were calculated. To assess the consistency of generated maps to lung physiology and the potential impact of non-rigid registration, visual analysis and quantitative comparison with non-registered data were performed. Results Perfusion images showed a continuous negative anterior-posterior gradient, majored on the AC mean map. Perfusion standard deviation maps showed higher variability in the periphery of the lungs, but especially in the posterior areas. The ventilation mean map showed a slightly positive anterior-posterior gradient on NoAC mean ventilation map, while the AC mean map showed no gradient. The NoAC ventilation SD map showed a higher variability in the periphery of the lungs. No statistical difference was found between the anterior posterior gradient measured on generated maps and the mean gradient of non-registered data. Conclusion We proposed a methodology to create statistical normal maps for V/Q SPECTs. Maps were consistent with the known physiological non uniformity and showed the impact of attenuation correction on the anterior-posterior gradient. These maps could be used for a Z-score analysis, and a better segmentation of healthy uptake areas.